THE DIFFERENCE OF ABNORMAL RETURNS BETWEEN BEFORE AND AFTER THE FRIDAY EFFECT IN THE INDONESIA STOCK EXCHANGE (EVENT STUDY OF CONSUMPTION SECTOR COMPANIES IN JAKARTA ISLAMIC INDEX IN 2018 - Dewi Astuti; Muhammad Nafik Hadi Ryandono (Universitas Airlangga, 2020)
Friday effect is a form of a market anomaly (deviation) that is contrary to the efficiency market, marked by high stock returns on Friday. The Friday effect phenomenon is an event or strategy which, if predictable, will be used by investors to get more profit (abnormal profit). This study aims to look at the effect of the Friday effect on abnormal returns in the consumption sector companies in the Jakarta Islamic Index (JII) in 2018, which is shown by whether there are differences in abnormal returns before and after Friday. The approach used in this study is a quantitative approach and testing the hypotheses that have been set. The method used is event study, with an observation period of 9 days, namely t - 4 (4 days before Friday), t = 0 (on Friday / event date) and, t + 4 (4 days after Friday). Hypothesis testing uses paired samples t-tests. The results of this study are based on these statistical tests with a significant level (α) = 0.05 producing a probability value of 0.784. This means that there is no difference in abnormal returns before and after Friday trading.Keywords: Friday Effect, Abnormal return, event study, Efficient Market, Jakarta Islamic Index (JII)REFFERENCE Fakhruddin, T. D. (2011). Pasar modal di Indonesia. Jakarta: Salemba Empat.Gumanti, T. A. (2011). Manajemen investasi: Konsep, teori dan aplikasi. Jakarta: Mitra Wacana Media.Lestari, W. R. (2011). Pengaruh weekend effect terhadap return saham di Bursa Efek Indonesia. Jurnal manajemen dan Keuangan, 9(1), 31-41.Luhgiatno. (2011). Analisis weekend effect terhadap return saham di Bursa Efek Indonesia. Fokus Ekonomi, 7(1), 2-3. DOI: https://doi.org/10.34152/fe.7.1.%25pSutedi, A. (2011). Pasar modal syariah: Sarana investasi keuangan berdasarkan prinship syariah. Jakarta: Sinar Grafika.